اسلامی قانون میں تعزیز بالحبس اور معاصرعدالتی کارروائیاں : ایک مطالعہ: The Nnotion of Imprisonment in Islamic Sharī̒ah and Contemporary Judicial Procedures (Al-Qamar, 2021)
Islam has presented the theory of punishment based on actions and deeds. According to Islamic system of criminal justice, nobody will be punished until and unless his action is proved in the court of law. Punishment again is based on the nature of the crime. In the result of judgement if someone is put into prison, they will remain in it until the completion of the sentence. This article is addressing some bad effects of this type of punishments which is in the form of imprisonment. A prisoner cannot participate in any social activity for example, in a social gathering, he can also not help his family in any financial matters. On the other hand, prisoner cannot do any religious activity like funeral prayer etc. He can also not visit any patient in the hospital. Therefore, for this reason a proposal and suggestion are presented to government that this punishment in the form of imprisonment should be kindly reviewed and there should at least be some kind of relaxation for all prisoners.
Keywords: Imprisonment; Ta̒ zīr; Judicial Procedure; Sharī̒ ah